Geographical Condition And Port Development - Zhein Adhi Mahendra Setiawan; Yuichiro Yoshida (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
The first-time purposely build container ships introduced in 1967 with a draft of 9 meters, and now, newer container ship drafts can reach 16 meters and more. The development of the container ship dimension is rapid. Ports respond to these changes and keep up with the more significant size and a deeper draft of the new container ship design. Ports are developing their infrastructure from installing gantry cranes to dredge their seafloor. This research reviews that phenomenon and studied how ports adapt to the changing container ship dimension, especially for Post Panamax container ships built for efficiency. To do that, we use an exogenous variable of ports' depth from 1972 to 1985 before the ports knew that they would need deeper depth to accommodate such ships. We find that ports with actual depth more or equal to 13.716 meters is significantly affected port to accommodate Post Panamax container ship in this present time. The scope of this research is to show how a port responds to the change of the dimension of a container ship. Nevertheless, this research can be a steppingstone to measure the causality of trade that never has been done correctly before by introducing an exogenous variable that is strong, which port’s depth regarding the Post Panamax container ship draft.